Identifying maternal needs following childbirth: comparison between pregnant women and recent mothers - Justine Slomian; Jean-Yves Reginster; Patrick Emonts; Olivier Bruyère (BMC, 2021)
Abstract Background The postnatal period is associated with new needs for mothers. Four categories of needs were highlighted in a previous study: for information, for psychological support, for the sharing of experiences and for practical and material support. To ensure that these four needs are inherent to the postpartum period, the aims of this study is to examine these needs by comparing recent mothers' needs with the needs of pregnant women. Methods The 4 needs previously identified were cross-sectionally investigated by online self-reported questionnaires completed by women in their last trimester of pregnancy and by mothers who had a child between 0 and 6 months of age. Results The 4 needs were largely present during the postpartum period. The need for information seemed to be more present during pregnancy (92.4 %) than during the postpartum period (84.6 %, p = 0.03), but women used the Internet significantly more often to search for information after childbirth (54.8 %) than during pregnancy (41.2 %, p < 0.0001). The needs for psychological support and to share experiences seemed to be closely linked. Even if the global satisfaction with psychological support was fairly high, it weakened after childbirth (p < 0.05). Feelings of loneliness (p < 0.0001) and depression scores (p = 0.01) were also higher during the postpartum period than during pregnancy. Finally, the need for practical support was also more pronounced during the postpartum period than during pregnancy (p = 0.01). Conclusions All mothers seem to meet the 4 identified needs during the postpartum period but at different levels of intensity. Trying to meet these needs could offer an opportunity to improve mothers' quality of life.